2017
DOI: 10.1136/bmj.j3876
|View full text |Cite
|
Sign up to set email alerts
|

Suicide on TV: minimising the risk to vulnerable viewers

Abstract: International media guidance should be strengthened, implemented, and enforced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…36 This outcome might have helped mitigate any harmful consequences of 13 Reasons Why. Furthermore, mental health and suicide prevention organizations shared material for educating teachers, adolescents, clinicians, and parents about how to discuss the show in schools, 3 and Netflix added content warnings to the show in May 2017. 37 Although it is impossible to account for all potential confounding variables, it is notable that the timing, specificity, and magnitude of the associations observed here are all consistent with a potential contagion by media.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 This outcome might have helped mitigate any harmful consequences of 13 Reasons Why. Furthermore, mental health and suicide prevention organizations shared material for educating teachers, adolescents, clinicians, and parents about how to discuss the show in schools, 3 and Netflix added content warnings to the show in May 2017. 37 Although it is impossible to account for all potential confounding variables, it is notable that the timing, specificity, and magnitude of the associations observed here are all consistent with a potential contagion by media.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Observers have called for nationwide analyses of death data given the widespread belief that 13 Reasons Why could trigger suicides in the vulnerable younger population. 3,15,16 Such studies had not been possible until the recent release of 2017 suicide data by the Centers for Disease Control and Prevention.…”
mentioning
confidence: 99%
“…Recently, the release of the Netflix show 13 Reasons Why , which depicts the suicidal process of an American adolescent girl, provided an ecological example of the effect of a video suicide narrative at the population level. Indeed, several authors cautioned about the serious—albeit potentially mixed [22,23,24]—impact of the series on youths’ mental health [25]. In the months following the broadcast, Niederkrothentaler et al found that suicide rates among those aged 10–19 years were 13% higher than expected from secular trends [14].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the 13 Reasons Why controversy, the British Medical Journal (BMJ), in an editorial titled ‘Suicide on TV: minimizing the risk to vulnerable viewers’ (Arendt et al, 2017), called for better implementation of international standards to regulate how television and movie producers represent suicide on screen. According to the authors, the Netflix series could trigger ‘self-harm among vulnerable viewers by romanticizing suicide and portraying it as the only option to cope with negative experiences’ (Arendt et al, 2017: para 2). For this reason, it is argued that ‘clinicians need to be aware of heightened media attention to adolescent suicide and ask vulnerable young patients about possible exposure so that potentially harmful effects can be minimized’ (Arendt et al, 2017: para 6).…”
mentioning
confidence: 99%